Genetic variability of the fifth generation of nile tilapia Oreochromis niloticus using microsatellite DNA markers - Satriani, Gloria Ika; Soelistyowati, Dinar Tri; Hardianto, Dian; Aliah, Ratu Siti (Jurnal Akuakultur Indonesia, 2011)
ABSTRACTFifth generations of Nile tilapia from several strains have been produced by using selective breeding program in Main Centre for Freshwater Aquaculture Development (MCFAD) Sukabumi, West Java. This research was aimed to evaluate the impact of family selection program of some highly economic traits on its genetic variability using microsatellite DNA markers. The total of 180 specimens have been collected from fifth generation of nine reciprocal mating between three families selected from fourth generation of Nile tilapia and were screened for genetic variability at three microsatellite loci (UNH 123*, UNH 172*, UNH 216*). The results showed that the amount of genetic variability on fifth generations of Nile tilapia from three strains was ranged between 33 to 100% and the highest genetic distance relationship between families was 0.3875. This research approved that females and males issued from the family which have more amount of genetic variability and higher distance to others could be considered as genetic materials to produce the next generation.Keywords: microsatellite DNA, genotype, genetic variability, genetic distance, Oreochromis nilotiocus ABSTRAKBeberapa strain ikan nila generasi kelima telah dihasilkan dalam program pemuliaan di Main Centre untuk Freshwater Aquaculture Development (MCFAD) Sukabumi, Barat Jawa. Riset ini bertujuan untuk mengevaluasi pengaruh seleksi famili terhadap performa karakter ekonomis penting berdasarkan keragaman genetiknya menggunakan penanda microsatellite DNA. Spesimen dari 180 individu generasi kelima hasil persilangan resiprokal antara tiga famili generasi keempat dianalisis dengan penanda tiga microsatellite loci (UNH 123*, UNH 172*, UNH 216*). Hasil penelitian menunjukkan bahwa keragaman genetik ikan nila generasi kelima berkisar antara 33 sampai 100% dan hubungan kekerabatan genetik antar famili yang paling jauh adalah 0,3875. Individu betina dan jantan yang berasal dari famili dengan tingkat keragaman genetik dan kekerabatan yang lebih tinggi dapat dipertimbangkan sebagai sumber genetik berkualitas untuk menghasilkan generasi berikutnya.Kata kunci: microsatellite DNA, genotipe, keragaman genetik, jarak genetik, Oreochromis nilotiocus